TAX IMAGE OF THE COUNTRY AND BUSINESS IN THE CONDITIONS OF EUROPEAN INTEGRATION - Revenko , O.; Revenko , T. (Pressing Problems of Public Administration, 2020)
Important institutes for economic development are taxes, which need more of attention and reform, taking into attention their impact on the tax image and socio-economic development of the country. An effective element in creating a positive vision of Ukraine for foreign countries (especially for investing and doing business here) is the tax image. If the priority goal of raising it is set, its elements will be reformed and improved. These elements include tax culture, tax potential, competitiveness, tax system and tax policy. The achievement of a certain result will also be facilitated by the general improvement of the economic situation of the country, which in one way or another depends on the image. In the future, this will have a positive impact on the general tax culture of the population, and may even change the general mentality and tax awareness of citizens. The components of national tax image formation and tax image of business are theoretically substantiated, which allows to identify their influence on the mechanism of ensuring tax competition of the country under integration conditions. Therefore, on the basis of the conducted analysis, it is proved that improvement of the Ukrainian tax image is possible by further reforming the system of tax authorities, ensuring its stability, improving the quality of client-oriented activity, and continuing digitalization of all tax procedures. The general features and tax aspects of social responsibility in the framework of measures applied by the business in the conditions of the coronavirus pandemic in European countries and in Ukraine are determined. It also further developed the definition of strategic conditions for creating a tax image of a business, taking into attention the concept of social responsibility. It has been proved that under integration conditions social responsibility in the tax sphere is able to ensure the unity of legal and moral and ethical values in the field of doing business and transparency of economic relations and trust in the investment sphere.